Caring for those in crisis : facing ethical dilemmas with patients and families - Mottram, Kenneth P., 1953- (Grand Rapids, Mich. : Brazos, 2007)
"Kenneth Mottram writes to better equip pastors and church leaders to minister to patients and their families in times of crisis and confusion. He provides a Christian model for ethical decision making; addresses such issues as organ donation, living wills, and withdrawing life support, offers counsel on helping patients and families face mortality, and gives practical advice on hospital visitation, prayer, and serving as advocate for the family to the medical staff."--BOOK JACKET.
Meeting an ethical dilemma -- Orientation to medical ethics -- Advocacy, trauma, and personal awareness -- A biblical look at ethics and advocacy -- The medical understanding of spirituality -- Frequently encountered ethical problems -- A decision-making model for ethical dilemmas -- Christian distinctives in facing ethical dilemmas -- Ethical issues in death and dying -- Spiritual interventions by the advocate.
"A pastor's guide"--Cover.
Includes bibliographical references.
Keywords: Pastoral medicine; Sick -- Pastoral counseling of; Patients -- Pastoral counseling of; Church work with the sick; Church work with families; Medicine -- Religious aspects -- Christianity; Medical ethics